Modelling Water Allocation for a Run-of-the-River Rice Irrigation Scheme Using GIS - Kamal, Md. Rowshon (2006)
Water is becoming increasingly scarce and it is important to find methods to reduce water consumption. It is a well-known fact that in most run-of-the-river irrigation projects, the water demands seldom satisfactorily match the erratic flows in the river. In large-scale irrigation schemes like the Tanjung Karang Rice Irrigation Scheme, allocation of water resources is more difficult due to the variability of water use, typical irrigation supply and the pattern of water availability. Due to unreliable water supply in the absence of storage reservoir for the scheme, there is a need for daily prediction and allocation of the available water resources equitably and efficiently to improve the system management. A study was attempted to develop Geographical Information System (GIS) integrated with water allocation model for ensuring equitable supply and efficient use of available water resources.